CLINICAL PROFILE AND VISUAL OUTCOME AFTER ERM REMOVAL- AN EXPERIENCE FROM A TERTIARY CARE REFERRAL CENTER IN NORTH INDIA - Shabnum nabi Var; Perveiz Ahmad Handoo (Indonesian Vitreoretinal Society, 2022)
Introduction: ERM is a cellular proliferation on the inner retinal surface and possesses contractile properties which leads to variable visual symptoms. Method: Thirty-four patients affected with epiretinal membrane were enrolled in this study. All patients underwent standard three port pars plana vitrectomy using standard 23-gauge instruments. Both ERM and ILM peels were performed in a circumferential pattern around the fovea. Patients were followed for 6 months. The visual outcome measures included postoperative logMAR visual acuity. The anatomical outcome was measured as decrease in foveal thickness on spectral domain optical coherence tomography (SD-OCT). Perioperative factors including duration of symptoms, preoperative visual acuity, etiology, membrane type and leakage on fundus fluorescein angiogram were correlated with the final visual outcomes. Results: The mean age of the patients in this study was 60.25 17.5 years with a range of 16 to 80 years. 19 patients (56%) were males. 33 patients had a unilateral ERM and 1 patient had an ERM in both eyes. Diminution of vision was the most common symptom in 34 patients, distortion of vision (metamorphopsia) was seen in 20 (58.8%) patients. The mean pre-operative log MAR best corrected visual acuity (BCVA) was 1.4±0.77 and the mean post-operative log MAR best corrected visual acuity (BCVA) was 0.9 ±0.63. Out of 34 patients in our study, 31 (91.2%) had improvement in VA, and the remaining 3 (8.82%) patients had no improvement and none of the patients had decreased vision. 16 patients had ≥2 lines of improvement in visual acuity. 15 patients had less than 2 lines of improvement. Conclusion: ERMs pose a significant risk to compromise the vision and affect varied age groups. ERM removal through standard three port pars plana vitrectomy offers an effective and safe procedure with better post operative visual outcomes.